2018
DOI: 10.3390/su10124667
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Superfood Ingredients—the Case of Bread in Germany

Abstract: Although there is no legal definition of the word 'superfood', in recent years exotic foods and ingredients have become popular in German food retailers. The aim of the study was to determine consumer preferences for superfood ingredients in different types of bread; to accomplish this, a choice experiment was set up with a representative sample of 503 German consumers. Respondents had to choose between products with varying attributes such as type of bread, superfood ingredient, nutritional information, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…Consumers' place of living emerged among the first three most important influencing factors for nine diseases, whereas in two cases, consumers' BMI rating and perception of income, and in one case, the identity of the primary grocery shopper, were among the most important influencing factors. Contrary to previous results [30][31][32][33], which found that an important factor in the consumption of functional foods is the gender of the consumer, in our analysis this factor was not among the top three factors influencing prediction for any of the diseases.…”
Section: Random Forest With the Aim Of Identifying Factors That Influcontrasting
confidence: 99%
See 3 more Smart Citations
“…Consumers' place of living emerged among the first three most important influencing factors for nine diseases, whereas in two cases, consumers' BMI rating and perception of income, and in one case, the identity of the primary grocery shopper, were among the most important influencing factors. Contrary to previous results [30][31][32][33], which found that an important factor in the consumption of functional foods is the gender of the consumer, in our analysis this factor was not among the top three factors influencing prediction for any of the diseases.…”
Section: Random Forest With the Aim Of Identifying Factors That Influcontrasting
confidence: 99%
“…Thus, we can emphasize that in the case of these diseases, it is important that companies address their prevention-related communication primarily at women. This result is in line with previous literature [30][31][32][33][34], which state that women are more open to functional food; at the same time, our results provide a more nuanced picture in that they identify the diseases for the prevention of which functional food development should be targeted to women.…”
Section: Disease Prevention With Functional Foods-consumers' Charactesupporting
confidence: 92%
See 2 more Smart Citations
“…Consumers' perceptions of the health benefits of crops are important in understanding preferences (Meyerding et al., 2018) and evaluating the strength and weaknesses of the product in a market (Sabbe, 2009), particularly when opening up new product markets (Thome‐Ortiz et al., 2019).…”
Section: Introductionmentioning
confidence: 99%